2013
DOI: 10.1073/pnas.1300769110
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and CDK-1 regulate cortical release of WRM-1/β-catenin to control cell division orientation in early Caenorhabditis elegans embryos

Abstract: In early Caenorhabditis elegans embryos, the Wingless/int (Wnt)-and Src-signaling pathways function in parallel to induce both the division orientation of the endomesoderm (EMS) blastomere and the endoderm fate of the posterior EMS daughter cell, called E. Here, we show that, in addition to its role in endoderm specification, the β-catenin-related protein Worm armadillo 1 (WRM-1) also plays a role in controlling EMS division orientation. WRM-1 localizes to the cortex of cells in both embryos and larvae and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…At the onset of M-phase, in response to P2-EMS signaling, WRM-1 disappears from the posterior cortex of EMS proximal to P2. After division, WRM-1 accumulates asymmetrically to higher levels in the nucleus of the posterior daughter cell E relative to the anterior daughter MS. 37,38 This asymmetric nuclear localization of WRM-1 depends on both Wnt signaling and Src-signaling. On the other hand, the asymmetric cortical disappearance of WRM-1 depends primarily on Wnt signaling, suggesting that these 2 localizations of WRM-1 are regulated independently.…”
Section: Asymmetric Localization Of Wrm-1/β-catenin Depends On Cdk-1 mentioning
confidence: 99%
See 3 more Smart Citations
“…At the onset of M-phase, in response to P2-EMS signaling, WRM-1 disappears from the posterior cortex of EMS proximal to P2. After division, WRM-1 accumulates asymmetrically to higher levels in the nucleus of the posterior daughter cell E relative to the anterior daughter MS. 37,38 This asymmetric nuclear localization of WRM-1 depends on both Wnt signaling and Src-signaling. On the other hand, the asymmetric cortical disappearance of WRM-1 depends primarily on Wnt signaling, suggesting that these 2 localizations of WRM-1 are regulated independently.…”
Section: Asymmetric Localization Of Wrm-1/β-catenin Depends On Cdk-1 mentioning
confidence: 99%
“…On the other hand, the asymmetric cortical disappearance of WRM-1 depends primarily on Wnt signaling, suggesting that these 2 localizations of WRM-1 are regulated independently. 38 In genetic backgrounds where WRM-1 remains cortical, such as in Wnt signaling mutants, removal of the parallel Src-signaling pathway results in a highly penetrant defect in aligning the EMS mitotic spindle to the anterior-posterior axis. Significantly, removal of WRM-1 activity from these mutant backgrounds was found to rescue the spindle orientation defect, supporting a negative role for cortical WRM-1 in regulating spindle rotation in EMS.…”
Section: Asymmetric Localization Of Wrm-1/β-catenin Depends On Cdk-1 mentioning
confidence: 99%
See 2 more Smart Citations
“…56 As a final example, it has also been observed that the ortholog of b-catenin in C.elegans controls cell division orientation in early embryos. 57 In mammals, a connection between AJ proteins and intracellular asymmetry during cell division and cell fate has been observed in certain tissues, but mostly characterized in stratified epithelia. For example, in embryonic neural stem cells, it has been documented that AJs are organized into different microdomains that are split unequally during asymmetric cell divisions by the cleavage plane.…”
Section: Links Between Cadherin-catenins and Positioning Of Mitotic Smentioning
confidence: 99%